2014
DOI: 10.1074/jbc.m114.566794
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-agonist Peroxisome Proliferator-activated Receptor γ (PPARγ) Ligand UHC1 Blocks PPARγ Phosphorylation by Cyclin-dependent Kinase 5 (CDK5) and Improves Insulin Sensitivity

Abstract: Background: PPAR␥ ligands can be used in numerous metabolic syndromes. Results: A novel non-agonist PPAR␥ ligand, UHC1 exhibited great beneficial effects on glucose metabolism and anti-inflammatory response. Conclusion: UHC1 shows anti-diabetic action by blocking CDK5-mediated PPAR␥ phosphorylation. Significance: UHC1 can be a novel therapeutic agent for use in type 2 diabetes and related metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 40 publications
2
87
0
Order By: Relevance
“…Interestingly, SR1664 and SR1824 were structurally very similar to the above-mentioned telmisartan [74], a well-characterized selective modulator of PPARg ( Figure 3, Table 1). A derivative of SR1664, UHC1, was later suggested as a more efficient antidiabetic and anti-inflammatory molecule [78]. Recently, using virtual screening methods tailored for PPARg [79], further selective agonists that inhibit phosphorylation of PPARg at serine 273 were shown to produce antidiabetic effects in vivo, such as the compounds F12016 [80] and L312 [81].…”
Section: Junmentioning
confidence: 99%
“…Interestingly, SR1664 and SR1824 were structurally very similar to the above-mentioned telmisartan [74], a well-characterized selective modulator of PPARg ( Figure 3, Table 1). A derivative of SR1664, UHC1, was later suggested as a more efficient antidiabetic and anti-inflammatory molecule [78]. Recently, using virtual screening methods tailored for PPARg [79], further selective agonists that inhibit phosphorylation of PPARg at serine 273 were shown to produce antidiabetic effects in vivo, such as the compounds F12016 [80] and L312 [81].…”
Section: Junmentioning
confidence: 99%
“…This paradigm has already been explored as a potential therapeutic target for T2D using the non-agonist PPAR gamma ligand UHC1, which exclusively prevents the phosphorylation of S273 on PPAR gamma. As a result, UHC1 treatment not only improved insulin sensitivity but also reduced diet-induced obesity, which is quite different from the TZDs (Choi, et al 2014b). In addition to providing mechanistic insight into how TZDs and PPAR gamma are involved in the progression of diabetes, these studies also implicate Thrap3 and CDK5 as prospective anti-diabetic targets as well.…”
Section: Ppar Gamma: New Mechanisms For Generating Insulin-sensitizinmentioning
confidence: 92%
“…These differences in ERK activation could possibly explain some of the efficacy and safety differences among existing synthetic TZDs. Recently, several PPARγ ligands have been found that promote insulin sensitization with fewer side effects in T2DM rodent models (123, 124). Whether these ligands can activate GPR40 or/and ERK has not been reported.…”
Section: Gpr40 and Pparγ An Integrated Two-receptor Signaling Patmentioning
confidence: 99%